Squamous Cell Carcinoma Arising from Mature Cystic Teratoma of Ovary (Community Based Medical Journal, 2025)
Squamous cell carcinoma of the ovary is a rare condition and usually arises in mature cystic teratoma (MCT) or dermoid cyst of the ovary. 0.17%-0.2% of mature cystic teratoma of the ovary (MCTO) undergo malignant transformation of which 80% are squamous cell carcinoma (SCC) transformation in MCTO. A case of SCC arising in a dermoid cyst of the ovary is being presented here. A 65-year-old post-menopausal lady presented with the complaints of pain and lump in the lower abdomen since 5 months. According to examination made on women and pelvic scanning, a 15 cm complex mass was found in the left adenexa of the patient. Final histopathology was reported as squamous cell carcinoma of left ovary arising from dermoid cyst. The prognosis of the malignant transformation of MCT depends on surgery stage; however it is extremely poor. The patient should receive chemotherapy regardless of stage.  CBMJ 2025 January: Vol. 14 No. 01 P: 182-185